Analysis of Peroxide Numbers and Free Fatty Acids in Unbranded Bulk Cooking Oil in Traditional Markets: Analisis Bilangan Peroksida Dan Asam Lemak Bebas Pada Minyak Goreng Curah Tidak Bermerek Di Pasar Tradisional - Greiszya Priskila; Petrus Darmawan (Jurnal Kimia dan Rekayasa, 2022)
Unbranded bulk cooking oil is widely sold in traditional markets at low prices. Cooking oil sold in the market must meet the quality set by the government, where cooking oil that does not meet the requirements will have an impact on health. The parameters used to determine the quality of cooking oil include the content of free fatty acids and peroxide numbers. The purpose of this study is to determine the levels of free fatty acids and peroxide numbers in unbranded bulk cooking oil and to determine whether the unbranded bulk cooking oil meets the requirements of SNI 7702: 2012. Determination of free fatty acids is done by the alkalimetry method using ethanol 95% neutral and PP indicator 1% then titrated with a standard NaOH solution to a pink color. The determination of the peroxide number was carried out by the iodometric method with the addition of glacial acetic acid: isooktan and saturated KI which was then titrated with a standard solution of sodium thiosulfate with the addition of 1% amylum indicator until the blue color disappeared. The results showed that all unbranded bulk cooking oil samples sold in the traditional market in Jebres Subdistrict, Surakarta had met the requirements for free fatty acid parameters, while for peroxide numbers only contained 1 sample that met the requirements of the seven samples, namely samples from the E market. AbstrakMinyak goreng curah tidak bermerek banyak dijual dipasar tradisional dengan harga yang murah. Minyak goreng yang dijual dipasaran harus memenuhi mutu yang ditetapkan oleh pemerintah, dimana minyak goreng yang tidak memenuhi persyaratan akan berdampak bagi kesehatan. Parameter yang digunakan untuk menentukan kualitas minyak goreng antara lain adalah kandungan asam lemak bebas dan bilangan peroksida. Tujuan penelitian ini adalah mengetahui kadar asam lemak bebas dan bilangan peroksida dalam minyak goreng curah tidak bermerek dan untuk mengetahui apakah minyak goreng curah tidak bermerek tersebut sudah memenuhi persyaratan SNI 7702:2012. Penentuan asam lemak bebas dilakukan dengan metode alkalimetri menggunakan etanol 95% netral dan indikator PP 1 % kemudian di titrasi dengan larutan standar NaOH sampai warna merah muda. Penetapan bilangan peroksida dilakukan dengan metode iodometri dengan penambahan asam asetat glasial : isooktan dan KI jenuh yang kemudian dititrasi dengan larutan standar natrium tiosulfat dengan penambahan indikator amylum 1% sampai warna biru hilang. Hasil penelitian menunjukan semua sampel minyak goreng curah tidak bermerek yang dijual di pasar tradisional Kecamatan Jebres, Surakarta telah memenuhi syarat untuk parameter asam lemak bebas, sedangkan untuk bilangan peroksida hanya terdapat 1 sampel yang memenuhi syarat dari ke tujuh sampel, yaitu sampel dari pasar E.